2021
DOI: 10.1017/s0033291721003925
|View full text |Cite
|
Sign up to set email alerts
|

Continuities in maternal substance use from early adolescence to parenthood: findings from the intergenerational cohort consortium

Abstract: Background This study assessed the extent to which women's preconception binge drinking, tobacco use and cannabis use, reported prospectively in adolescence and young adulthood, predicted use of these substances during pregnancy and at 1 year postpartum. Methods Data were pooled from two intergenerational cohort studies: the Australian Temperament Project Generation 3 Study (395 mothers, 691 pregnancies) and the Victorian Intergenerational Health Cohort Study (398 mothers, 609 pregnancie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…29 We have also shown that for most mothers, perinatal alcohol (65%), tobacco (90%) and cannabis (59%) use is commonly preceded by preconception use, which was also prospectively assessed in adolescence and young adulthood. 30 We have further shown important associations between prospectively assessed preconception parental mental health histories and relational and child outcomes. A history of persistent symptoms of depression or anxiety predicted poorer emotional bonding with infants at 1 year post-birth in both mothers and fathers (β range =−0.42 to −0.55).…”
Section: Findings To Datementioning
confidence: 69%
See 1 more Smart Citation
“…29 We have also shown that for most mothers, perinatal alcohol (65%), tobacco (90%) and cannabis (59%) use is commonly preceded by preconception use, which was also prospectively assessed in adolescence and young adulthood. 30 We have further shown important associations between prospectively assessed preconception parental mental health histories and relational and child outcomes. A history of persistent symptoms of depression or anxiety predicted poorer emotional bonding with infants at 1 year post-birth in both mothers and fathers (β range =−0.42 to −0.55).…”
Section: Findings To Datementioning
confidence: 69%
“… 29 We have also shown that for most mothers, perinatal alcohol (65%), tobacco (90%) and cannabis (59%) use is commonly preceded by preconception use, which was also prospectively assessed in adolescence and young adulthood. 30 …”
Section: Findings To Datementioning
confidence: 99%
“…Overall, 1 out of the 14 general cohort studies (not including the 2 alcohol-focused studies) included information on alcohol exposure pre-pregnancy recognition; however, the level of alcohol consumed was not examined. Notably, two of the more recently conducted smaller cohort studies examined these periods, and generated estimates similar to the alcohol-focused studies [ 128 , 129 ]. Considering the potential impacts of PAE on birth outcomes, and the known influence of both timing and exposure threshold, the variability in data collection methods may limit the clinical relevance of findings [ 51 , 163 ].…”
Section: Discussionmentioning
confidence: 92%
“…Where data for overall prevalence were not reported for n > 1000 participants (The Barwon Infant Study and NDSHS Cohort from 2010), these results were also excluded from the meta-analysis. Findings from 55 small cohort studies (<1000 participants) and/or case-control studies were reported by 59 publications, from which all relevant data were extracted and tabulated ( Supplementary Tables S8 and S9 ) [ 18 , 19 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation